Out-of-hours palliative care provided by GP co-operatives: availability, content and effect of transferred information - Deliens Luc; Schweitzer Bart; Blankenstein Nettie; Horst Henriette (BMC Palliative Care, 2009)
Abstract Background Out-of-hours GP care in England, Denmark and the Netherlands has been reorganised and is now provided by large scale GP co-operatives. Adequate transfer of information is necessary in order to assure continuity of care, which is of major importance in palliative care. We conducted a study to assess the availability, content and effect of information transferred to the GP co-operatives. Methods Cross-sectional exploratory study of all palliative care phone calls during a period of one year to a GP co-operative. Results The total number of phone calls about patients who needed palliative care was 0.75% of all calls to the GP co-operative. Information was transferred by GPs on 25.5% of palliative care patient calls, and on 12% of palliative care patient calls from residential care homes. For terminally ill patients the number of information transfers increased to 28.9%. When information was transferred, the content consisted mainly of clinical data. Information about the diagnosis and current problems was transferred in more than 90% of cases, information about the patient's wishes in 45% and information about the patient's psychosocial situation in 30.5% of cases. A home visit was made after 53% of the palliative care calls. When information was transferred, fewer patients were referred to a hospital. Conclusion GPs frequently fail to transfer information about their palliative care patients to the GP co-operatives. Locums working at the GP co-operative are thus required to provide palliative care in complex situations without receiving adequate information GPs should be encouraged and trained to make this information available to the GP co-operatives.